2017
DOI: 10.1002/app.45966
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of a superabsorbent slow‐release fertilizer with sodium alginate and biochar

Abstract: A novel hydrogel was synthesized through the graft copolymerization of acrylic acid (AA) and acrylamide (AM) onto sodium alginate with ammonium persulfate as the initiator, methylene bisacrylamide as the crosslinking agent, and calcium chloride as the precipitating agent. Rapeseed meal biochar made at 300 °C was also used. A series of graft copolymers with various molar ratio of AA to AM was prepared. The structures of the hydrogels were characterized by Fourier transform infrared spectroscopy and scanning ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In view of the economic and environmental factors, abundant natural materials including lignin and montmorillonite (Mt) have been considered to be ideal carriers for slow‐release urea fertilizers. Lignin is a natural organic polymer that is abundantly available as a byproduct of the production of wood pulp . Moreover, lignin is a renewable, biodegradable, eco‐friendly, and amorphous biopolymer for soluble fertilizer .…”
Section: Introductionmentioning
confidence: 99%
“…In view of the economic and environmental factors, abundant natural materials including lignin and montmorillonite (Mt) have been considered to be ideal carriers for slow‐release urea fertilizers. Lignin is a natural organic polymer that is abundantly available as a byproduct of the production of wood pulp . Moreover, lignin is a renewable, biodegradable, eco‐friendly, and amorphous biopolymer for soluble fertilizer .…”
Section: Introductionmentioning
confidence: 99%
“…In the equilibrium condition, the phosphorus concentration found was 2.5 mg L −1 . BaKi et al (2018) observed a similar behavior for SHAs based on polyacrylamide grafted with sodium alginate and biochar [ 73 ]. The slow release of fertilizer is important to ensure better nutrient absorption and minimize nutrient loss [ 74 ].…”
Section: Resultsmentioning
confidence: 92%
“…This indicates that the sawdust contains cellulose, hemicellulose, and lignin. In the infrared spectrum of the SW-AA-AM polymer, the peaks at 3443 and 1677 cm −1 were caused by the stretching vibration of –NH in acrylamide and the stretching vibration of the amide group (–CONH 2 ), respectively [39,43]. The new peak at 1409 cm −1 was assigned to the stretching vibration of C–N in acrylamide.…”
Section: Resultsmentioning
confidence: 99%